The Role of Teleradiology in the COVID-19 Pandemic - Çoraplı, Mahmut; Oktay, Cemil; Çil, Ercan; Çoraplı, Gökhan; Bulut, Hacı Taner (Cerrahpaşa Medical Journal, 2021)
Objective: This study aimed to investigate the role of teleradiology during the COVID-19 pandemic in Turkey. Methods: We evaluated chest computed tomography images of 1649 patients whose diagnoses of COVID-19 had been confirmed with the reverse transcription-polymerase chain reaction, using the COVID-19 imaging categories proposed by the Radiological Society of North America. Two staff radiologists independently evaluated the images, and the 2 results were compared. Disagreements were adjudicated by a third staff radiologist. This final consensus was used to evaluate the agreement between the computed tomography images and the teleradiology reports. Results: There was an excellent and statistically significant agreement between the observers (κ = 0.847, P < .001). Similarly, there was a very high agreement between observer 1 and observer 2, and the final consensus (κ = 0.934, P < .001; κ = 0.891, P < .001, respectively). There was an excellent and statistically significant agreement between the consensus decisions and the teleradiology reports (κ = 0.832, P < .001). Conclusion: There was an excellent interobserver agreement between the teleradiology assessments made during the COVID-19 pandemic and the assessments made by staff radiologists, as per the classification system proposed by the Radiological Society of North America. Our results support the suggestion that teleradiology can safely be used during pandemics. Cite this article as: Çoraplı M, Oktay C, Çil E, Çoraplı G, Taner Bulut H. The Role of Teleradiology in the COVID-19 Pandemic. Cerrahpaşa Med J. 2021;45(2):80-86.